96.4k views
5 votes
1. -3 - 3x = -4(2x + 7)

User Egalth
by
5.0k points

2 Answers

1 vote

-3 - 3x = -4(2x + 7)

Multiply both sides by -4

(-4)(2x)=-8x

(-4)(7)=-28

-3-3x=-8x-28

Move -8x to the other side. Sign changes from -8x to +8x.

-3-3x+8x=-8x+8x-28

-3-3x+8x=-28

-3+5x=-28

Move -3 to the other side. Sign changes from -3 to +3.

-3+3+5x=-28+3

5x=-28+3

5x=-25

Divide both sids by 5

5x/5=-25/5

Answer :x=-5

User Matvore
by
5.0k points
3 votes

Answer:

x = -5

Explanation:


-3 - 3x = -4(2x + 7)\\-3 - 3x = -4(2x) -4(7)\\-3 - 3x = -8x - 28\\5x = -25\\x = (-25)/(5) = -5

User Vongo
by
5.0k points